New versus Frequent Donors: Exploring the Behaviour of the Most Desirable Donors. Issue 3 (August 2016) - Faulkner, Margaret; Romaniuk, Jenni; Stern, Philip
While there is no shortage of worthy recipients for prosocial behaviour, there is a constant battle to attract and keep donors. This research examines both money and blood donor behaviour for two key groups, new donors, (to grow the donor base), and frequent donors (to secure current support streams). We draw on over 1.2 million records from a U.S. health related charity for a three-year timeframe; and records of all Australian blood donors (1.1 million) for a five-year timeframe. We show the law-like patterns that underpin brand growth in other markets also apply in the non-profit sector. The vast majority of new donors give just once or twice a year with few giving at higher frequency levels. The stability of donation churn across blood and money suggests a structural norm in behaviour over time rather than an outcome of marketing activity. We discuss implications for resource allocation and marketing strategies.